Robots and Employment: Evidence from Japan, 1978–2017 - Adachi, Daisuke; Kawaguchi, Daiji; Saito, Yukiko U. (Journal of Labor Economics, 2024)
This paper studies the relationship between industrial robots and employment in Japan on the basis of a unique dataset that allows us to calculate the unit price of robots. Our model combines standard factor demand theory with a recent task-based approach to derive a simple estimation equation between robot prices and employment, and our identification strategy leverages heterogeneous applications of robots across industries and heterogeneous price changes across applications. We find that the decline in robot prices increased both the number of robots and employment by raising the productivity and production scale of robot-adopting industries.